Teleost and elasmobranch eye lenses as a target for life-history stable isotope analyses - Katie Quaeck-Davies; Victoria A. Bendall; Kirsteen M. MacKenzie; Stuart Hetherington; Jason Newton; Clive N. Trueman (PeerJ, 2018)
Incrementally grown, metabolically inert tissues such as fish otoliths provide biochemical records that can used to infer behavior and physiology throughout the lifetime of the individual. Organic tissues are particularly useful as the stable isotope composition of the organic component can provide information about diet, trophic level and location. Unfortunately, inert, incrementally grown organic tissues are relatively uncommon. The vertebrate eye lens, however, is formed via sequential deposition of protein-filled fiber cells, which are subsequently metabolically inert. Lenses therefore have the potential to serve as biochemical data recorders capturing life-long variations in dietary and spatial ecology. Here we review the state of knowledge regarding the structure and formation of fish eye lenses in the context of using lens tissue for retrospective isotopic analysis. We discuss the relationship between eye lens diameter and body size, describe the successful recovery of expected isotopic gradients throughout ontogeny and between species, and quantify the isotopic offset between lens protein and white muscle tissue. We show that fish eye lens protein is an attractive host for recovery of stable isotope life histories, particularly for juvenile life stages, and especially in elasmobranchs lacking otoliths, but interpretation of lens-based records is complicated by species-specific uncertainties associated with lens growth rates.